Global requirements for manufacturing and validation of clinical grade extracellular vesicles - Abhimanyu Thakur; Deepika Rai (The Journal of Liquid Biopsy)
Extracellular vesicles (EVs) are nanovesicles released from different cell types from biofluids such as blood, urine, and cerebrospinal fluid. They vary in size and biomarkers, and their biogenesis pathways allow them to be divided into three major types: exosomes, micro-vesicles, and apoptotic bodies. EVs have been studied in the context of diagnosis and therapeutic intervention of various pathological conditions such as cancer, neurodegenerative diseases, and pulmonary diseases. However, the production of EV-based therapeutics can be affected by the source, heterogeneity, or disease, raising questions about the manufacturing and validation of EVs of clinical grade and their scope regarding good manufacturing practice (GMP) in the industry. To address this, we have discussed the state-of-the-art requirements for EV production that must occur in a GMP-compliant environment with a reliable and traceable source. Additionally, EVs' homogeneity and the therapeutics' purity and stability must be analyzed and validated. Quality control measures must also be established to ensure the safety and efficacy of EVs. In conclusion, these considerations must be weighed carefully when manufacturing and validating EVs of clinical grade to ensure their safety and efficacy for therapeutic use.